The legacy of one-room schoolhouses: A comparative study of the American Midwest and Norway - Leidulf Mydland (European Journal of American Studies)
In the history of education the one-room schoolhouse has played an important role in several countries. In the rural areas of the US Midwest and in Norway the one-room schoolhouse was the most common school in the second half of the nineteenth century and the first decades of the twentieth. Although the schoolhouses at first sight seem identical there are some interesting points of distinction in their educational history and how their legacy is interpreted, managed, preserved and promoted today. In the Midwest they are a beloved national icon, often listed, embodying national values and virtues. In Norway their story is effectively untold, not a single one is listed on national preservation lists and by no means do they embody national identity, virtues or values. This article offers an explanation for this different treatment.